Actor-Reality Construction – A pragmatic constructivist approach to management and accounting - Nørreklit, Hanne (Proceedings of Pragmatic Constructivism, 2011)
This article elaborates on the profile of the Research Group for Actor-Reality Construction, addresses the scope of ProPraCon, and discusses emerging research themes within pragmatic constructivism.